حرکتِ معنا در کالبدِ لفظ: سنجشِ تطبیقیِ مثنویِ معنوی و تفسیرِ قرآنی — ایک لسانی و عرفانی تجزیہ: The Movement of Meaning within the Body of Words: A Comparative Study of the Mathnawī and Tafsīr Rūh al-Bayān (Al-Qamar, 2024)
This paper presents a comparative study of Rumi’s Mathnawi and Ismail Haqqi’s Tafsir Ruh al-Bayan, focusing on the dynamic movement of meaning within linguistic form. It argues that both texts conceive meaning as a living process that unfolds through narrative, symbolism, and spiritual commentary. By analyzing thematic parallels and interpretive strategies, the study shows how poetic and exegetical discourses converge in their treatment of divine revelation and spiritual insight. The Mathnawi employs storytelling and metaphor to animate meaning, while Ruh al-Bayan integrates mystical interpretation within Qur’anic exegesis. Together, they illustrate a shared hermeneutical vision in which words serve as vessels for spiritual transformation. This research contributes to comparative studies of Sufi literature and Qur’anic interpretation.
Keywords: Mathnawi, Ruh al-Bayan, Meaning, Comparative Study, Sufi Exegesis